Peningkatan Kualitas Sumber Daya Manusia Melalui Kegiatan Kuliah Kerja Nyata Dengan Pembinaan Perempuan dan Anak Usia Dini Serta Pembaharuan Peta Wilayah Administrasi di Desa Liang Kecamatan Kota Bangun - Wijayansyah, Harry Guntur; Lestari, Windari Ayu; Rahmawati, Septia; Tombang, Resti Altadarista; Kapuangan, Almadania Belhasni; Saputra, Yoga Tri; Sitorus, Sondang Pebrian (B-Creta Publisher, 2024)
Liang Village is one of the villages in Kota Bangun District. With an area reaching 4,783 hectares. Liang Village is one of the villages located in Kota Bangun District, Kutai Kartanegara Regency, East Kalimantan Province. Meanwhile, in implementing KKN, the methods chosen are basic data, problem information, program determination and program implementation. Program implementation for each work program was carried out in stages, following the results of group discussions and carried out in an orderly manner in accordance with the 49th KKN implementation schedule. The results of the KKN work program implementation were carried out successfully and smoothly. The implementation of real work courses for the 49th class of Mulawarman University has been carried out for more than 45 days. Implementation of the work program offered is a solution and effort in empowering women and early childhood to prepare quality human resources in the future. Meanwhile, in its implementation, the work program has various outputs ranging from creative videos, scientific journals, pocket books, recycled crafts, products to designs which are hoped to provide social engineering benefits, especially in educating the public about awareness of the importance of improving self-quality. Apart from that, the output that we are highlighting is a map of updated regional boundaries that has been used at the village office.